ANALISA PENGGUNAAN TRANSISTOR 2N3055 DAN TEC (THERMOELECTRIC COOLER) SEBAGAI BAHAN ALTERNATIF PANEL SEL SURYA (SOLAR CELL) - Muhammad Agus Sahbana; Akhmad Farid (Polinema Press, Politeknik Negeri Malang, 2021)
The renewable energy has a very important role in meeting energy needs. This is because the use of fuel for conventional power plants in the long term will deplete the dwindling resources of oil, gas and coal and can also cause environmental pollution. Solar panels based on 2N3055 transistors and Thermoelectric Cooler (TEC) are the basic materials for designing alternative power plants. In the manufacturing process, this solar panel utilizes electronic components that are capable of generating electrical energy (emf), so that it can be used as an appropriate technology to produce a solar panel that utilizes solar energy in the form of heat and solar radiation. The use of transistors 2N3055 and TEC proved to be more efficient in generating electrical energy, there was no significant decrease in voltage and current even though the weather was suddenly cloudy. The average voltage and current generated in this solar panel are 24.58 VDC and 2.72 Ampere DC.